Bridging Spatiotemporal Scales of Normal Fault Growth During Continental Extension Using High‐Resolution 3D Numerical Models. (5th July 2022) - Pan, Sophie; Naliboff, John; Bell, Rebecca; Jackson, Chris
Abstract: Continental extension is accommodated by the development of kilometer‐scale normal faults, which grow during meter‐scale slip events that occur over millions of years. However, reconstructing the entire lifespan of a fault remains challenging due to a lack of observational data with spatiotemporal scales that span the early stage (<10 6  yrs) of fault growth. Using three‐dimensional numerical simulations of continental extension and novel methods for extracting the locations of faults, we quantitatively examine the key factors controlling the growth of rift‐scale fault networks over 10 4 –10 6  yrs. Early formed faults (<100 kyrs from initiation) exhibit scaling ratios consistent with those characterizing individual earthquake ruptures, before evolving to be geometrically and kinematically similar to more mature structures developed in natural fault networks. Whereas finite fault lengths are rapidly established (<100 kyrs), active deformation is transient, migrating both along‐ and across‐strike. Competing stress interactions determine the distribution of active strain, which oscillates between being distributed and localized. Higher rates of extension (10 mm yr −1 ) lead to more prominent stress redistributions through time, promoting episodic localized slip events. Our findings demonstrate that normal fault growth and the related occurrence of cumulative slip is more complex than that currently inferred from displacement patterns on now‐inactive structures, which only provide a space‐ and time‐averaged picture of fault kinematics and related seismic hazard. Plain Language Summary: When the Earth's tectonic plates are stretched, they crack along fractures called faults. We have a general understanding that faults grow over millions of years by slipping during earthquakes. However, we don't yet know how earthquake slip on the scale of meters accumulate to form faults that are up to a few hundred kilometres‐long, and which offset the Earth's surface by several kilometres. We developed numerical models that simulate tectonic stretching and fracturing of the Earth's plates. The models produce fault patterns similar to those seen in the Earth. Importantly, early modeled timesteps reproduce the same geometries associated with individual earthquake slip. We show that the style in which slip accumulates is more complex than that inferred by fault growth models, which only provide a space‐ and time‐averaged picture. Stress‐interactions between individual faults are critical, causing different faults to slip at different times. This leads to time periods where slip occurs along many small faults, and other periods of time when slip is focused on large faults. Variations in the number and size of faults that are slipping have implications for assessing earthquake hazard. Fault interaction may better our understanding of complex, often unexpected earthquakes that rupture along multiple faults. Key Points: Normal fault growth is poorly understood due to the lack of spatially and temporally constrained observational datasets Three‐dimensional numerical modeling reveals that fault patterns are rapidly established (<100 kyrs) and active deformation is highly transient Fault interaction and strain migration are key elements of fault network growth and related seismic hazard